The MYH9 Gene and MYH9 rs12107 Gene Polymorphism are associated with MYH9 mRNA Underexpression in Non-syndromic Cleft Lip and Palate among Indonesian Deutero-Malay Subrace - Saskia Lenggogeni Nasroen; Jeffrey Jeffrey; Dewi Lidya Ichwana Nasution; Kayla Keishafa Siti Hallina; Annisa Namira; Unik Imiati Nurfadhillah (UPT Publikasi Ilmiah Universitas Islam Bandung, 2026)
Genetic factors play a significant role in non-syndromic cleft lip and palate (NS-CLP) as a common congenital orofacial malformation. The myosin heavy chain 9 (MYH9) gene is one of the candidate genes associated with NS-CLP. This study aimed to investigate changes in MYH9 gene mRNA expression in the oral epithelium of NS-CLP, to analyze the MYH9 rs12107 polymorphism as a risk factor for NS-CLP, and to associate each genotype of this polymorphism with MYH9 gene mRNA expression in the Indonesian Deutero-Malay population. This study is a case-control design with 60 samples: 30 NS-CLP subjects and 30 control subjects. All subjects were from the Deutero-Malay subrace, which is the majority subrace in Indonesia. For mRNA expression analysis, RNA was isolated from the oral epithelium of all subjects, and real-time (RT) polymerase chain reaction (PCR) was performed. The mRNA expression changes were analyzed using the Livak method (2−ΔΔCt), and statistical analysis was performed using the Mann-Whitney test. For the MYH9 rs12107 gene polymorphism, DNA was isolated from venous blood, followed by PCR and Sanger sequencing. Chi-square test was used to analyze allele and genotype frequencies. In general, MYH9 mRNA expression was 0.39 times lower in the NS-CLP compared to the control (underexpression), with a significant difference (p=0.001). For the MYH9 rs12107 gene polymorphism, it was shown that the T mutant allele (OR=1.217, p=0.658) was more in NS-CLP than in control, the CT genotype (OR=0.545, p=0.273) was more in control than in NS-CLP, and the TT genotype (OR=1.529, p=0.426) was more in NS-CLP than in control. The mRNA expression values for the CT and TT genotypes of MYH9 rs12107 were 0.239 and 0.178 lower in NS-CLP than in control (underexpression). In conclusion, among the Indonesian Deutero-Malay subrace, the MYH9 gene was underexpressed in NS-CLP, and the MYH9 rs12107 polymorphism was associated with underexpression in the CT and TT genotypes.